1999
DOI: 10.1007/s004649901181
|View full text |Cite
|
Sign up to set email alerts
|

The risk of gallbladder perforation at laparoscopic cholecystectomy

Abstract: Inflammation and a positive history of previous laparotomies play a crucial role in GB perforation at LC. Hydropic GB was the most accurate predictor of rupture. A prospective trial is needed to confirm the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 10 publications
0
28
0
2
Order By: Relevance
“…16 Perforation occurs in 13%-50% of patients who undergo laparoscopic cholecystectomy, and in 10%-40% of these patients, bile leakage and stone spillage are present. 17 Laceration due to grasper traction and electrocautery dissection is the most common mechanism of gallbladder rupture during laparoscopic cholecystectomy.…”
Section: Recherchementioning
confidence: 99%
“…16 Perforation occurs in 13%-50% of patients who undergo laparoscopic cholecystectomy, and in 10%-40% of these patients, bile leakage and stone spillage are present. 17 Laceration due to grasper traction and electrocautery dissection is the most common mechanism of gallbladder rupture during laparoscopic cholecystectomy.…”
Section: Recherchementioning
confidence: 99%
“…This is consistent with one study 17 and would be in keeping with the assertion that hydrops of the gallbladder is a principal cause of perforation. 25 Calik et al 21 showed no difference in perforation rates. This finding may be due to the inclusion of fewer overfilled gallbladders.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of significant difference may also be confounded by the lack of overfilled gallbladders seen at time of operation. 25 Our summative outcome would suggest that although ASP decreases dissection time, the additional time taken to aspirate the gallbladder may cancel out any advantage gained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations